Financial Stability, Financial Target, and External Pressure on Financial Statement Fraud: An Empirical Study of Mining Companies Listed on the Indonesia Stock Exchange (2019–2023) - Salim, Wetika Yolinsia; Reniati; Sumiyati (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2025)
There are a lot of expectations and obligations on businesses when it comes to reporting their finances. Management engages in financial statement fraud to conceal unsavory financial realities since the public expects the company's financial statements to be valuable in every way. Financial stability, financial goals, and external pressure are the variables that this research hopes to identify as having an impact on the likelihood of fraudulent financial statements. Financial stability, financial goals, and external pressure are the independent factors in this research, with financial statement fraud as the dependent variable. This study employs a purposive sample strategy for data collection, a quantitative research methodology for hypothesis testing, and binary logistic regression for analysis. This study found that among mining companies listed on the Indonesia Stock Exchange between 2019 and 2023, financial statement fraud was positively impacted by the financial stability variable, but unaffected by the financial target and external pressure variables.